Epistemologi Tindakan Muhammad Iqbal - Ja?far, Suhermanto (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2015)
This paper highlights Iqbal?s epistemology which focuses on the question of metaphysic and ontology. To understand the absolute being, Iqbal starts from intuition about human beings? ego engaged at reality of the absolute ego. Intuition can reveal the absolute reality or the real super ego. The real existence of reality is spiritual. The true reality, according to Iqbal, refers to the existence of God, man and nature. However, the real existence of reality is a manifestation of the absolute reality. It is an absolute being or an absolute ego. Intuition about self itself brings man to the intuition of ultimo reality. Iqbal?s epistemology of self (ego) is essentially talking about the philosophy of the human that focuses on self or ego. Self or ego is the starting point for Iqbal to relate between God and nature. Life in the universe, according to Iqbal, is a series of actions. All of these are for the benefit of mankind as a co-creator through the meaningful action. The meaningful action is a foundation of human existence in manifesting himself. Iqbal formulates this meaningful action as a manifestation of the way the human utilizes to face with the reality of the other. To Iqbal, meaningful action is charged with the ontological-religious content which emphasizes the fundamental spiritual aspect of Islam with the term ?amal (noble conduct). To him, meaningful action will be always imprinted in people?s lives and only the meaningful action alone that can help people prepare themselves to face the destruction of their bodies.